Evaluation of congenital heart disease clinically and by echocardiography in children of age group 0-12 years - Kondapalli, Chandra Sekhar; Gondi, Kalyan Chakravarthy; Madana, Sravya (International Journal of Contemporary Pediatrics, 2019)
Background: The present study was conducted to evaluate clinical and echo-cardio graphic findings of congenital heart disease in children of age-group 0-12 years attending present hospital. Methods: A study was done at Katuri Medical College and hospital in 65 patients aged 0-12 years; both sexes; for a period of 2 years. study design is exploratory, with proforma been designed to study congenital heart diseases. Alexander Nada’s criteria is used. Results: Out of 4145 cases; 65 cases aged 0-12 years have congenital heart disease over a period of 2 years; (acyanotic 55 cases and cyanotic 10 cases). 23 cases are between 1-5 years and 20 cases are >5 years; 1/3rd cases diagnosed before 1 year of age. male 40 cases and female 25 cases. Urban cases-27 and rural cases are 38.48 cases have consanguinity and family history in 12 cases. extra cardiac manifestations in 6 cases. Normal sized heart with normal vascularity of lung was seen in 14 / 65 cases. 51/65 cases showed various radiological features depending on type of lesion based on echo findings. Among the ACHDs VSD was the commonest CHD seen in children. Among the cyanotic heart diseases TOF was the commonest CHD observed, comprising of 6 cases. Conclusions: Chest X-ray was abnormal in 80% of cases with increased CT ratio in 58.3% cases. ECG was abnormal in 73.3% of cases and majority of them had left axis deviation.95%of CHDs, including ACHDs and CCHDs which were diagnosed clinically include ASD, VSD, PDA, AS, PS, CoA, TOF, TGA. Most common clinically diagnosed CHD was VSD. Clinico echo correlation was accurate in 75% cases. Clinico echo correlation was highest with isolated lesions like VSD, ASD and in cases with typical findings like CoA, PDA, AS, TOF and least with multiple lesions or atypical findings.